Influence of genetic polymorphism on sports talent performance versus non-athletes: a systematic review and meta-analysis - Ferreira, C. P.; Silvino, V. O.; Trevisano, R. G.; de Moura, R. C.; Almeida, S. S.; dos Santos, M. A. P. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Talented athletes exhibit remarkable skills and performance in their respective sports, setting them apart from their peers. It has been observed that genetic polymorphisms can influence variations in sports performance, leading to numerous studies aimed at validating genetic markers for identifying sports talents. This study aims to evaluate the potential contribution of genetic factors associated with athletic performance predisposition in identifying sports talents.